(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article discusses linguistic basis of teaching foreign languages ​​in the context of multilingualism. The focus is on the formation of individual multilingualism of citizens through the development of linguistic attention and transfer of linguistic knowledge as well as skills in languages.